2013
DOI: 10.1051/0004-6361/201220362
|View full text |Cite
|
Sign up to set email alerts
|

Two radio supernova remnants discovered in the outer Galaxy

Abstract: Context. New and existing large-scale radio surveys of the Milky Way at centimetre wavelengths can play an important role in uncovering the hundreds of expected but missing supernova remnants in the Galaxy's interstellar medium. We report on the discovery of two supernova remnants (SNRs) designated G152.4−2.1 and G190.9−2.2, using Canadian Galactic Plane Survey data. Aims. The aims of this paper are, first, to present evidence that favours the classification of both sources as SNRs, and, second, to describe ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
2
27
1
Order By: Relevance
“…It is the faintest SNR yet observed, with a radio surface brightness at 1 GHz of Σ 1 GHz 1.1 × 10 −23 W m −2 Hz −1 sr −1 , a factor of three below the previous faintest known SNRs of Foster et al (2013). G181.1+9.5 presents a rare opportunity to study SNR evolution and offshoot topics (such as reverse-shock heating of explosion ejecta, suggested by the X-rays in the object's centre) in a uniquely pristine environment that is much different from the Galactic plane ISM.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is the faintest SNR yet observed, with a radio surface brightness at 1 GHz of Σ 1 GHz 1.1 × 10 −23 W m −2 Hz −1 sr −1 , a factor of three below the previous faintest known SNRs of Foster et al (2013). G181.1+9.5 presents a rare opportunity to study SNR evolution and offshoot topics (such as reverse-shock heating of explosion ejecta, suggested by the X-rays in the object's centre) in a uniquely pristine environment that is much different from the Galactic plane ISM.…”
Section: Discussionmentioning
confidence: 73%
“…Over the last 15 yr, a total of 14 new SNRs and pulsar wind nebulae have been found in the Outer Milky Way Galaxy mostly with data from the Canadian Galactic plane Survey (Kothes et al 2001(Kothes et al , 2005Kothes 2003;Tian et al 2007;Foster et al 2013;Gerbrandt et al 2014). SNR G181.1+9.5 is, however, no ordinary SNR.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2011) identified two new faint SNRs G25.1−2.3 and G178.2−4.2. Supplemented by the Urumqi λ6 cm data, Foster et al (2013) 1 http://zmtt.bao.ac.cn/6cm/ identified another two new SNRs G152.4−2.1 and G190.9−2.2 from the Canadian Galactic Plane Survey (CGPS) data. With the Giant Meterwave Radio Telescope, Roy & Pal (2013) have recently discovered a young SNR G354.4+0.0 in the central region of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…5 +3.2, G150.5+3.8, and G160.1−1.1 (Gerbrandt et al 2014),a n dG 1 5 2 . 5 −2.1 (Foster et al 2013). Other SNR discoveries in the CGPS data were reported by Kothes et al (2001), Kothes (2003),K o t h e s et al (2005),T i a ne ta l .…”
Section: Structures Of Intermediate Sizementioning
confidence: 98%